A review of community playgroup participation. Issue 2 (June 2020) - McLean, Karen; Edwards, Susan; Mantilla, Ana
Community playgroups, which are one type of playgroup and early childhood service, operate on a weekly basis under the leadership of volunteer caregivers (including parents, kinship members, family-day carers and other adults in children's lives). Caregivers and children voluntarily attend and participate in community playgroups. Although community playgroups operate throughout Australia and similar models exist internationally, little is known about the benefits and/or otherwise of community playgroup participation for children, families and communities. A review of the research into community playgroup participation, specifically research investigating children and families' participation in community playgroups published between 2000 and 2018, is reported in this paper. The findings from the five peer-reviewed papers identified through the search provide directions for further research needed to build the evidence base for community playgroup participation.